THE RELATIONSHIP OF COPING MECHANISM AND SELF EFFICACY IN TUBERCULOSIS PATIENTS: A CROSS-SECTIONAL STUDY - Miftahul Falah; Tukimin Bin Sannsuwito; Regidor III Dioso; Lilis Lismayanti; Nina Pamela Sari (Journal of health research and technology, 2024)
Tuberculosis (TB) is a contagious infectious disease caused by mycobacterium tuberculosis. TB sufferers feel sad because they receive statements about disease transmission which can give rise to negative perceptions and cause stress. Effective coping mechanisms can influence the patient's self-efficacy towards healing. The aim of this research is to analyze the relationship between coping mechanisms and self-efficacy in TB sufferers at the Tamansari Public Health Center, Tasikmalaya City, Indonesia. The population in this study was people with TB disease. Total sample was 41 respondents with a random sampling technique. Quantitative research and cross-sectional method used in this study. The research results showed that the majority of TB sufferers had adaptive coping mechanisms with high self-efficacy. The results of the Chi-Square test obtained a p-value of 0.001 < 0.05, meaning that there was a relationship between coping mechanisms and self-efficacy in TB sufferers. Coping mechanisms can influence sufferers' self-confidence in their abilities, adaptive coping mechanisms can make TB sufferers have high self-confidence to achieve optimal recovery. The results of this research are expected to play a role in providing health education and family support to sufferers to increase sufferers' confidence in recovery.